Prevalence of gastrointestinal and blood parasites in horses of Nakhon Si Thammarat province, Thailand - Tanakorn Phetkarl; Punpichaya Fungwithaya; Kittima Lewchalermvong; Narin Sontigun (My University, 2024)
The global prevalence of gastrointestinal (GI) and blood parasite infections in horses is a significant concern due to their substantial impact on morbidity, mortality, and economic losses in the horse industry. In Thailand, limited research has been conducted on these parasites in horse populations, and data from southern Thailand are lacking. Consequently, this study aimed to estimate the prevalence of GI and blood parasites in horses in Nakhon Si Thammarat province, Thailand. In total, 79 fecal and blood samples were collected from horses across 11 farms in Nakhon Si Thammarat province. The fecal examination was conducted using simple flotation, formalin-ethyl acetate sedimentation, and a modified McMaster technique. Conventional polymerase chain reaction (PCR) was used to identify blood and strongyle parasites. The influence of sex, age, and body condition score on the prevalence of GI parasites was also analyzed. Six GI parasites were detected: four nematodes (Oxyuris equi, Parascaris equorum, strongyles, and Strongyloides westeri), one trematode (Gastrodiscus aegyptiacus), and one protozoan (Eimeria leuckarti). The overall prevalence of GI parasites was 74.7%, with single strongyle infections accounting for the highest proportion at 50.6%, followed by co-infections of strongyles and G. aegyptiacus at 10.1%. All 11 pooled strongyle samples were positive for cyathostomins and Strongylus vulgaris using conventional PCR with specific primers. Sex was significantly associated with the overall prevalence of GI parasites, whereas both sex and age were significant risk factors for infection by strongyle parasites. Theileria equi was the only blood parasite species detected in the surveyed horses, with a prevalence of 1.3% (n = 1/79). This study is the first to estimate the prevalence of GI and blood parasites in horses from Nakhon Si Thammarat province, Thailand. These findings highlight the importance of implementing control measures against GI parasites and are pivotal for developing effective infection prevention strategies.
Keywords: Prevalence; Veterinary Equine Medical Research